0205 Lung cancer risk among bricklayers in a pooled analysis of case-control studies. (23rd June 2014) - Consonni, Dario; De Matteis, Sara; Olsson, Ann; Pesch, Beate; Kromhout, Hans; Straif, Kurt; Brüning, Thomas
Abstract : Objectives: Bricklayers may be exposed to several lung carcinogens, including crystalline silica and asbestos. Previous studies reported an excess of lung cancer among these workers. We examined lung cancer risk among bricklayers within SYNERGY, a large international pooled analysis of case-control studies on lung cancer and the joint effects of occupational carcinogens (http://SYNERGY.iarc.fr ). Method: The pooled dataset included 15 608 cases and 18 531 controls from 22 centres in Europe, Canada, Hong Kong, and New Zealand. For men ever employed as bricklayers we estimated odds ratios (ORs) and 95% confidence intervals (CIs) adjusted for study centre, age, lifetime cigarette smoking history, and employment in occupations with exposures to known or suspected lung carcinogens. Results: We found 1322 cases and 1004 controls who had ever worked as bricklayers (OR: 1.35; 95% CI: 1.22–1.49). There was a clear positive trend with length of employment (P < 0.0001). The relative risk was higher for squamous (OR: 1.44, 95% CI: 1.28–1.63, 578 cases) and small cell carcinomas (OR: 1.60, 95% CI: 1.36–1.87, 248 cases), than for adenocarcinoma (OR: 1.14, 95% CI: 0.98–1.32, 289 cases) (P-value for homogeneity: 0.0007). ORs were still elevated after additional adjustment for education and in analyses using blue collar workers as referents. Conclusions: This study provided additional evidence of increased lung cancer risk in bricklayers. Although non-causal explanations cannot be completely ruled out, the association is plausible in view of the potential for exposure to several carcinogens, notably crystalline silica and to a lesser extent asbestos.